Anthropogenic impacts on shallow lake ecosystems in the middle Yangtze floodplain since the 19th century - Zeng, Linghan (2020)
The Yangtze floodplain lakes, which are important water resources in China, have been reported to suffer from eutrophication and water quality degradation. Palaeolimnological proxies including chlorophyll and carotenoid pigments, chironomids and stable carbon and nitrogen isotopes in dated sediment cores from six lakes with distinct catchment characteristics were analysed to investigate the influence of anthropogenic activities (agriculture, industry/urbanization, dam construction) and climate on algal community and lake ecosystems for sustainable development and water management purposes. Sedimentary TN and TP flux indicated increased nutrient loadings into the middle Yangtze floodplain lakes with the intensification of agricultural and industrial/urban activities in the catchments. Regression analysis showed that agricultural activities were the main source of N loading into the lakes, whereas large quantities of P were from urban/industrial point source. Mann-Kendall coefficients suggested an overall increase in algal production in these Yangtze floodplain lakes over the last two centuries. However, the timing and main driver of algal production increase were different. Generalized additive models (GAMs) and regression analysis showed that increasing N loading from agricultural activities was the main driver of the increases in algal production after ~ the 1940s CE in Honghu and Futou Lakes which are dominant in agricultural activities in the catchments. For Luhu and Wanghu Lakes where industrial and urban activities are dominant in the catchments, major increases in algal production started from ~ the 1980s CE due to the increasing nutrient (mainly P) loading with the intensification of urbanization/industrialization. With the intensification of human activities, algal production also increased in Dongting and Poyang Lakes since ~ the 1980s CE. However, the free hydrological condition concealed the influence of nutrient loading in these two lakes. After ~ 2000 CE, the disproportional increase of P relative to N from industrial and urban point sources resulted in the low sedimentary N: P ratios (< 10) and hence the increase in N2-fixing cyanobacteria (indicated by aphanizophyll) in Dongting, Poyang, Luhu and Wanghu Lakes. In contrast, the consistent N loading from agricultural activities led to the high sedimentary N: P ratios (> 15), and hence N2-fixing cyanobacteria were rare in Honghu and Futou Lakes. In the four lakes with potential HABs, concentrations and sedimentation rates of pigments were low in the large and open Dongting and Poyang Lakes than Luhu and Wanghu Lakes, resulting from the flush of nutrients and algae out of the lakes. Results of the UVR index showed that free hydrological connection with the Yangtze River, which leads to extensive water level fluctuations and high concentrations of suspended particle concentrations, resulted in low underwater light condition in the Yangtze floodplain lakes. Local dam construction which hydrologically isolated the lakes from the Yangtze River promoted the underwater light conditions in the Yangtze floodplain lakes, stimulating benthic communities as indicated by the increased abundance of macrophyte-related chironomids. Since the 1990s CE, underwater light condition deteriorated in the lakes with the increase in algal production due to the intensification of human activities in the catchments. For severely polluted lakes with potential HABs, local dam construction amplified the symptoms of eutrophication (Luhu and Wanghu Lakes), resulting in the shift from macrophyte-dominated state to algal dominated state as indicated by the transition in chironomid communities and the decrease in δ 13C. In contrast, the free hydrological connection with the Yangtze River may alleviate the eutrophication in Dongting and Poyang Lake as suggested by moderate abundance of macrophyte-related chironomids. For less polluted lakes (Honghu and Futou), the increase of macrophytes after local dam construction may buffer against eutrophication, maintaining the lakes in a macrophyte-dominate state as indicated by the high abundance of macrophyterelated chironomids and high values of δ 13C. This study demonstrates that nutrients from catchment anthropogenic activities are the fundamental factor influencing ecosystem structures in floodplain lakes, followed by hydrological modification caused by local dam construction. Compared with agricultural activities, urbanization and industrial activities are more likely to cause eutrophication and HABs. Free hydrological connection with the main channel is efficient at relieving the symptoms of eutrophication resulted from anthropogenic disturbance in floodplain lakes by flushing nutrients and algae out of the lake.